National trade unions and the ETUC: a history of unity and diversity (Brussels, 2017)
"This publication is a follow-up to the book 1973-2013: 40 years of history of the European Trade Union Confederation. It looks more closely at how different trade union models in different European countries, traditions and cultures have come together within this organisation.